2003
DOI: 10.1111/j.1741-3737.2003.00927.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Marriage Increase the Odds of Affluence? Exploring the Life Course Probabilities

Abstract: This study estimates the life course incidence and age pattern of affluence among American couples in comparison to nonmarried, never married, and formerly married men and women. Life course probabilities are computed from a series of life tables built upon 25 years of data from the Panel Study of Income Dynamics (N ϭ 8,510 25-yearolds; N ϭ 3,481 45-year-olds). Results confirm the notion that marriage enhances the lifetime probability of affluence, and that this advantage varies sharply by gender and by race. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 31 publications
3
53
1
2
Order By: Relevance
“…Although structural barriers to asset accumulation do exist (White & Rogers, 2000;Hirschl, Altobelli, & Rank, 2003), married couples save at higher rates than other types of families even after controlling for income, education, and other selection variables (Waite, 1995;Carney & Gale, 2001;Lupton & Smith, 2003). In addition, the longer spouses stay married, the more wealth they accumulate (Hao, 1996;Lupton & Smith, 2003).…”
Section: Are Assets and Consumer Debts Complements In Marriage?mentioning
confidence: 92%
“…Although structural barriers to asset accumulation do exist (White & Rogers, 2000;Hirschl, Altobelli, & Rank, 2003), married couples save at higher rates than other types of families even after controlling for income, education, and other selection variables (Waite, 1995;Carney & Gale, 2001;Lupton & Smith, 2003). In addition, the longer spouses stay married, the more wealth they accumulate (Hao, 1996;Lupton & Smith, 2003).…”
Section: Are Assets and Consumer Debts Complements In Marriage?mentioning
confidence: 92%
“…Moreover Mills and Daly's study shows that female respondents reports more negative prejudicial attitudes towards interracial relationships than male respondents (Mills and Daly 1995). Hirschl and others' study showed that marriage enhances the odds of affluence significantly for female and not as significantly for male; therefore the decision to marry becomes more important to female than male (Hirschl, Altobelli and Rank 2003). In a study which examines gender differences in desired characteristics when searching for a partner for both short term and long term relationship, the result showed that men focus more on physical attractiveness in general, while women focus more on earning capacity (Stewart, Stinnett and Rosenfeld 2000).…”
Section: Graph 1 Comparison Between the Respondents And The Originalmentioning
confidence: 99%
“…In this study, men have answered more positively towards interracial relationships in general compared to women. Considering that marriage may enhance the odds of affluence significantly for women and not as significantly for men, and consequently the decision to marry becomes more important for women than for men (Hirschl, Altobelli and Rank 2003), women may rationally prefer to date and marry someone from the same background, considering the different groups' perceived socioeconomic status; this rationality might have affected the way female respondents answered the questionnaire. The gender differences in attitudes and the actual number and pattern of interracial marriages in Sweden may have a correlation as well.…”
Section: Effect Of Background Variablesmentioning
confidence: 99%
“…PSID data have shaped a new and still emerging definition of economic well-being by transforming research in this area from a static and narrow view of rich and poor to a dynamic one in which families experience episodes of poverty or affluence (e.g., Brooks-Gunn and Duncan 1997;Hirschl et al 2003;Sandoval et al 2009;Rank and Hirschl 2014) and shocks to wealth (e.g., Stephens 2001;Conley and Thompson 2013). The growing number of three-and fourgeneration families is now supporting important new analyses of multigenerational associations in socioeconomic status attainment (e.g., Sharkey and Elwert 2011;Hertel and Groh-Samberg 2014;Pfeffer 2014;Wightman and Danziger 2014).…”
Section: Introductionmentioning
confidence: 99%